THE EFFECT OF SOCIAL MEDIA MARKETING, TRUST BRAND, AND WORD OF MOUTH ON PURCHASE DECISIONS (CASE STUDY AT REAL B DISTRO SURABAYA). - Risky Bahrudin Yusuf; Sengguruh Nilowardono (NAROTAMA UNIVERSITY, Indonesia, 2019)
The intention of consumer purchases is the willingness of a product to buy the goods they want. this is a strong determinant in the purchase of a product or brand. Therefore this study aims to analyze whethervariables social media marketing, brand trust, word of mouth can influence purchasing decisions to buy various Persebaya attribute products that are sold at Real B Distro Surabaya. This research is quantitative research with a sample of 160 respondents. Furthermore, the data were analyzed using multiple linear regression analysis techniques and classical assumption tests. The results showed that the three hypotheses proposed had a significant and supportive effect.